Scientific research conducted in the Surxon Valley from 1917 to 1941 and their importance - Nodira Xasanova ibragimovna (Zien Journals, 2022)
It is well-known that the Valley of Surxon had great natural resources, and the issue of studying and mastering them began as it was still during the chorism. (Matthew 24:14; 28:19, 20) In particular, the fertile soil of the valley, the hot climate, and the presence of large and slippery rivers indicated the prospects for the development of agriculture in the region. To that end, from 1913 to 1917, the Sherabad Convention conducted extensive research on the construction of irrigation facilities in the valley and the development of new lands.To the group of engineers, S. See P. Headed by Maksimov
Keywords: Denov; Eslibog; Ko'hitang